Green super-hydrophobic concrete with impermeability and self-healing property

By using a fluorine-free waterproofing agent in concrete, the problem of concrete being susceptible to moisture and corrosive ions is solved, and the preparation of green superhydrophobic concrete is realized, which extends the service life and reduces maintenance costs.

CN119430777APending Publication Date: 2025-02-14BEIHANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411874886.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Due to its porous structure and hydrophilicity, existing concrete materials are susceptible to erosion by moisture and corrosive ions, resulting in shortening of service life and increasing maintenance costs.

Method used

By adopting the configuration method of fluorine-free waterproofing agent, by mixing polydimethylsiloxane and stearic acid in a certain proportion and dispersing evenly in the cement mortar, a green superhydrophobic concrete with anti-seepage and self-healing properties is formed.

Benefits of technology

It achieves effective prevention of moisture and corrosive ions, extends the service life of concrete, reduces maintenance costs, and uses cheap and easy-to-get reagents for preparation of this material, which is simple in process and easy to promote and apply.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430777A_ABST
    Figure CN119430777A_ABST
Patent Text Reader

Abstract

The invention relates to green super-hydrophobic concrete with impermeability and self-healing property, novel environment-friendly super-hydrophobic concrete (SC-4) is prepared by adopting a specific body hydrophobic modification method, the water contact angle of the novel environment-friendly super-hydrophobic concrete is 155 degrees, and the sliding angle of the novel environment-friendly super-hydrophobic concrete is 8 degrees. The compressive strength (CS) of the SC-4 is 29.83 MPa, and the flexural strength (FS) of the SC-4 is 5.47 MPa. Due to the synergistic effect of wettability and mechanical properties, the SC-4 obtains excellent overall stability. A leaching test shows that the SC-4 has excellent impermeability, the accumulated water absorption rate of the SC-4 is 75% lower than that of common concrete (OC), and the accumulated NaCl absorption rate of the SC-4 is 80% lower than that of the common concrete (OC). After 200 times of high-strength load wear, the water contact angle of the sample is still kept at 150 degrees or above, and the corresponding mechanical property is also kept stable. Therefore, the SC-4 has excellent mechanical stability and self-healing property. An ultraviolet test shows that CS and FS of the aged SC-4 are only reduced by 7.9% and 4.4%, which indicates that the sample has very strong ultraviolet (340nm) resistance. The important contribution of the research lies in developing green super-hydrophobic concrete which is superior to traditional concrete in the aspects of durability and environmental aging resistance, meanwhile, an environment-friendly preparation method is adopted, and a solution with a wide prospect is provided for practical engineering application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] A green super-hydrophobic concrete material with impermeability and self-healing properties and a preparation method thereof belong to the fields of civil engineering, materials, new energy and environment. It can be mainly applied to building structures, road surfaces and bridges and dams. By obtaining this technology, the cement substrate can be greatly prevented from being eroded by moisture and corrosive ions, thereby being able to extend its service life and reduce maintenance costs. At the same time, the reagents used to prepare the green super-hydrophobic concrete are cheap and easy to obtain, and the preparation process is simple. It can be easily hardened using conventional processes and can be obtained after a certain period of maintenance, which makes this technology very easy to promote and apply. Background Art

[0002] Concrete is the most widely used civil engineering material in the world because of its good plasticity, impact resistance and wear resistance. Concrete is often used in outdoor facilities such as bridges, buildings and pavements. However, due to its porous internal structure and inherent hydrophilicity, long-term outdoor exposure allows water in nature (usually containing a large amount of chloride and magnesium ions) to penetrate into the interior of concrete, which may corrode and destroy the internal structure, greatly shortening the service life of concrete.

[0003] Studies have shown that water penetration is a key factor in shortening the service life of concrete. Therefore, effectively preventing water carrying corrosive ions from entering concrete can ensure the stability of the mechanical strength of concrete, thereby achieving the purpose of long-term use. With the advancement of interdisciplinary research, superhydrophobic materials based on the "lotus effect" have received widespread attention in the field of concrete due to their special water repellency. The water contact angle (WCA) of a superhydrophobic surface exceeds 150° and the sliding angle (SA) is less than 10°. In general, superhydrophobic materials have a multi-layered rough structure and low surface energy, which helps to form air pockets and help the surface produce a hydrophobic effect. At present, the waterproofing of concrete is mainly achieved through two ideas: (i) surface modification method; and (ii) intrinsic modification method. The surface modification method is to perform hydrophobic modification on the processed concrete surface. Superhydrophobic coatings are constructed on the concrete surface by spraying, dipping and template methods. There are also many reports on superhydrophobic concrete coatings. For example, Li et al. prepared BCP polymers by two-step hydrothermal preparation and coated BCP on the concrete surface, and finally constructed a micro / nano dual rough structure, which made the coating have good hydrophobicity. In addition, they also studied the chemical bonding between nanosilicon hydrophobic functional groups and cement hydration products on the concrete surface, proving that nanosilicon undergoes interfacial hydration in an alkaline environment. However, the poor adhesion between the coating and the substrate makes the super-hydrophobic coating prone to cracking, coating peeling and aging. These problems are usually not conducive to the long-term use of super-hydrophobic concrete.

[0004] In view of the problems existing in the surface modification method, the bulk modification method of concrete has been paid attention to and studied. The bulk modification method is to add a hydrophobic modifier during the preparation of concrete to make the entire concrete superhydrophobic concrete. For example, Wang's team reported superhydrophobic concrete based on bulk modification. They used saturated fatty acid lauric acid as a hydrophobic modifier to prepare superhydrophobic concrete. The superhydrophobic concrete prepared by this system showed excellent performance in corrosion resistance. In addition, Wei et al. directly used fluorinated 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane (PFDTES) as an added hydrophobic modifier to prepare white superhydrophobic concrete with a WCA of 152° and a SA of 7°. Although bulk-modified superhydrophobic concrete is superior to surface-modified superhydrophobic concrete in terms of aging resistance, durability, mechanical properties and corrosion resistance, it mostly uses fluorine-containing reagents. These reagents are not only expensive, but also pollute the environment. Therefore, it is very meaningful to use cheap and environmentally friendly reagents to prepare strong and corrosion-resistant superhydrophobic concrete. Summary of the invention

[0005] The present invention provides a green super-hydrophobic concrete with anti-seepage and self-healing properties, which specifically comprises the following steps:

[0006] S1. Preparation of fluorine-free waterproofing agent: Add polydimethylsiloxane and stearic acid into a beaker in a certain proportion to form a fluorine-free waterproofing agent;

[0007] S2. Preparation of the waterproofing agent mixture: Continue to add ethyl acetate to the beaker to disperse the fluorine-free waterproofing agent, and obtain a fluorine-free waterproofing agent mixture by stirring for 10 minutes using a magnetic stirrer and ultrasonically dispersing for 30 minutes;

[0008] S3. Preparation of super-hydrophobic cement mortar: 360 g of standard sand, 120 g of cement and 60 g of tap water (water-cement ratio of 0.5) were stirred at a slow speed in a cement mortar mixer for 5 minutes. The waterproofing agent mixture was poured into the mixer and further stirred at a high speed for 3 minutes to ensure that the fluorine-free waterproofing agent was evenly dispersed in the cement mortar to obtain super-hydrophobic cement mortar.

[0009] S4, mold cleaning: 40×40×160mm 3 and 40×40×40mm 3 The mold is cleaned and dried, placed in a plasma machine, and treated at a power of 500-600W for 100-120s;

[0010] S5, placing the cleaned stand-by mold on a vibration table, pouring the super-hydrophobic cement mortar described in step S3 into it and vibrating and compacting it for 2 minutes;

[0011] S6. After 24 hours, the hardened samples were taken out and placed in a curing room at a temperature of 25°C and a relative humidity of 95% for curing for 3, 7 and 28 days, and finally a green super-hydrophobic concrete with impermeability and self-healing properties was obtained.

[0012] The method for preparing green super-hydrophobic concrete with anti-seepage and self-healing properties is characterized in that the mass ratio of polydimethylsiloxane and stearic acid in step S1 is 0.5-4.5:0.58-30.69; the mass ratio of polydimethylsiloxane, stearic acid and ethyl acetate in step S2 is 0.5-4.5:0.58-30.69:5.07-30.42; the mass ratio of standard sand, cement and tap water in step S3 is 3:2:1.

[0013] The method for preparing the green super-hydrophobic concrete with anti-permeability and self-healing properties is characterized in that, in step S4, the cleaned and ready-to-use mold is placed on a flat workbench; the super-hydrophobic cement mortar described in step S3 is poured into a completely identical mold, and the super-hydrophobic cement mortar is stirred at a uniform speed for 2 minutes using a glass rod, so that the super-hydrophobic cement mortar is evenly spread from the center to the surrounding of the mold until the super-hydrophobic cement mortar completely fills the mold;

[0014] The method for preparing green super-hydrophobic concrete with anti-seepage and self-healing properties is characterized in that three molds (40×40×160mm 3 ) is placed on a standard vibration table and vibrated and compacted at a constant speed for 2 minutes.

[0015] The method for preparing green super-hydrophobic concrete with anti-seepage and self-healing properties is characterized in that three molds (40×40×160mm 3 ) is filled with 2084kg / m 3 .

[0016] The method for preparing green super-hydrophobic concrete with anti-seepage and self-healing properties is characterized in that three molds (40×40×40mm 3 ) is placed on a standard vibration table and vibrated and compacted at a constant speed for 2 minutes.

[0017] The method for preparing green super-hydrophobic concrete with anti-seepage and self-healing properties is characterized in that three molds (40×40×40mm 3 ) is filled with 2084kg / m 3 .

[0018] The method for preparing the green super-hydrophobic concrete with impermeability and self-healing properties is characterized in that in step S6, the hardened sample is placed in a curing room with a temperature of 25° C. and a relative humidity of 95% for continuous curing for 3, 7 and 28 days, and finally a green super-hydrophobic concrete with impermeability and self-healing properties is obtained.

[0019] The core key (general) step of the present invention is to add fluorine-free waterproofing agent NFWA (mainly composed of polydimethylsiloxane and stearic acid) before the hydration reaction of cement mortar. The homemade fluorine-free waterproofing agent (NFWA) is used as an external hydrophobic modifier to hydrophobically modify the hydrophilic cement mortar, and finally a strong green super hydrophobic concrete (SC-4) is prepared.

[0020] The purpose (mechanism) of this key step is to hydrophobically modify cement mortar with stearic acid (STA) by adding modified small molecules. Since STA hinders the formation of hydration products, the compact structure of concrete is reduced. However, because polydimethylsiloxane (PDMS) has good mechanical adhesion, the compact structure of modified concrete is compensated to a certain extent. Ultimately, superhydrophobic concrete not only ensures the basic hydrophobic function, but also gives the sample a certain mechanical stability by adding modified PDMS.

[0021] Advantages of patents:

[0022] The present invention adopts the method of STA / PDMS organic synergy, and uses the bulk modification method to prepare green super-hydrophobic concrete with impermeability and self-healing properties. Analysis shows that the water contact angle (WCA) of SC-4 reaches 155 degrees, and the sliding angle (SA) is 8 degrees. At 28 days, the compressive strength and flexural strength of SC-4 reached 29.83 MPa and 5.47 MPa, respectively, showing excellent mechanical properties. Thanks to the synergistic effect of hydrophobicity and mechanical properties, SC-4 has excellent comprehensive stability. In addition, leaching tests show that compared with ordinary concrete (OC), SC-4 has significantly better impermeability, the cumulative water absorption rate is reduced by 75%, and the cumulative NaCl absorption rate is reduced by 80%. After 200 high-intensity load wear cycles, the water contact angle of the SC-4 sample remains above 150 degrees, and its mechanical properties remain stable. This shows that SC-4 has excellent mechanical sustainability and self-healing properties. Subsequently, the results of UV aging tests showed that the compressive strength and flexural strength of the aged SC-4 were only 7.9% and 4.4% lower than those of the original sample, respectively. This confirms that SC-4 has strong UV resistance under 340-nanometer UV light. More importantly, SC-4 exhibits excellent comprehensive performance and environmentally friendly preparation technology, providing a strong guarantee for its wide application in practical engineering. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The SEM electron microscope images of the super hydrophobic concrete product obtained in Example 1, wherein (a) is a 40 micron SEM electron microscope image, and (b) is a 1 micron SEM electron microscope image.

[0024] Figure 2 (a) is the EDS element spectrum of the green super-hydrophobic concrete sample obtained in Example 1, and (b) is the EDS element spectrum of the conventional concrete sample.

[0025] Figure 3 This is the FTIR infrared spectrum of the green super hydrophobic concrete sample obtained in Example 1.

[0026] Figure 4 The wettability performance of the green superhydrophobic concrete samples obtained in Example 1, wherein (a) is the static wettability of the green superhydrophobic concrete (SC-4), (b) is the dynamic wettability of the green superhydrophobic concrete (SC-4), and (c) is the static wettability of the green superhydrophobic concrete prepared with different contents of stearic acid (STA).

[0027] Figure 5 The mechanical properties of the green super-hydrophobic concrete (SC-4) sample obtained in Example 1 are shown in Figure 1, where (a) is the compressive strength of SC-4 at different ages, and (b) is the flexural strength of SC-4 at different ages.

[0028] Figure 6 The water absorption rate at different times when the green super-hydrophobic concrete (SC-4) obtained in Example 1 is completely immersed in a deionized water solution.

[0029] Figure 7 The NaCl absorption rates at different times when the green super-hydrophobic concrete (SC-4) obtained in Example 1 is completely immersed in a 3.5% NaCl solution.

[0030] Figure 8 The comprehensive performance of the green super-hydrophobic concrete (SC-4) obtained in Example 1 under high-intensity load friction. (a) is the surface condition of the sample before and after friction, (b) is the actual image of the instrument used in the experiment, (c) is the wettability of the sample surface after wear, and (d) is the wettability change during wear.

[0031] Fig. 9 The mechanical properties test of the green super hydrophobic concrete (SC-4) after wear in Example 6, wherein (a) is the compressive strength of the SC-4 at different ages after wear, and (b) is the flexural strength of the SC-4 at different ages after wear.

[0032] Fig.10The performance of the green super-hydrophobic coagulant obtained in Example 1 changes with time during long-term irradiation with strong ultraviolet light (340 nm). (a) is the change in wettability of SC-4 with ultraviolet irradiation time, (b) is the compressive strength of SC-4 after ultraviolet irradiation, and (c) is the flexural strength of SC-4 after ultraviolet irradiation.

[0033] Example 1

[0034] Preparation of green super hydrophobic concrete:

[0035] Preparation of fluorine-free waterproofing agent: Add polydimethylsiloxane and stearic acid into a beaker in a mass ratio of 3.24:20 to form a fluorine-free waterproofing agent.

[0036] Preparation of the fluorine-free water repellent mixture: Continue to add 27 g of ethyl acetate into the beaker to disperse the fluorine-free water repellent, and obtain the fluorine-free water repellent mixture by stirring with a magnetic stirrer for 10 minutes and ultrasonic dispersion for 30 minutes.

[0037] Preparation of super hydrophobic cement mortar: 360 g of standard sand, 120 g of cement and 60 g of tap water (water-cement ratio of 0.5) were stirred in a cement mortar mixer at a slow speed for 5 minutes. The waterproofing agent mixture was poured into the mixer and further stirred at a high speed for 3 minutes to ensure that the fluorine-free waterproofing agent was evenly dispersed in the cement mortar to obtain super hydrophobic cement mortar.

[0038] Mold cleaning: 40×40×160mm 3 and 40×40×40mm 3 The mold is cleaned and dried, placed in a plasma machine, and treated at a power of 500-600W for 100-120s.

[0039] Place the cleaned mold on a vibration table, pour the super-hydrophobic cement mortar into it and vibrate and compact it for 2 minutes; take out the hardened sample after 24 hours, and place it in a curing room with a temperature of 25°C and a relative humidity of 95% for 3, 7 and 28 days, and finally obtain green super-hydrophobic concrete with impermeability and self-healing properties. The SEM electron microscope image, EDS energy spectrum image, and FTIR infrared spectrum image of the super-hydrophobic concrete are shown in Figure 2. Figure 1 (a) and (b), Figure 2 (a) and (b), Figure 3 show.

[0040] From the SEM electron microscope image, it can be seen that in the microscopic morphology of 40 microns of concrete, there are grooves of different lengths on the surface, and micro-nano clusters of different sizes are randomly distributed between the grooves, which respectively constitute the necessary rough structure of the hydrophobic function. From the EDS element spectrum, it can be concluded that the sample mainly contains elements C, O, Mg, Al, Si, and Ca, and the content of C, O, and Si elements is the highest in green super-hydrophobic concrete. From the FTIR infrared spectrum, it can be seen that green super-hydrophobic concrete is different from conventional concrete. It uniquely contains hydrophobic functional groups CH 3 and CH 2 The presence of these functional groups indicates that the fluorine-free waterproofing agent successfully modified the sample. This also proves that the excellent wetting performance of green superhydrophobic concrete is due to CH 3 and CH 2 caused by the presence of functional groups.

[0041] Example 2

[0042] Dynamic and static wettability of green superhydrophobic concrete surface

[0043] The green super-hydrophobic concrete (SC-4) with anti-seepage and self-healing properties prepared in Example 1 was subjected to a wettability test:

[0044] The excellent water repellency of superhydrophobic concrete can prevent water from carrying corrosive ions into the concrete, thus protecting its internal dense structure. The main components of the non-fluorine water repellent (NFWA) for superhydrophobic concrete used in this study are PDMS and STA, among which stearic acid STA is rich in hydrophobic long chains and is used to hydrophobically modify the concrete, while PDMS is flexible and chemically stable and is used to enhance the mechanical adhesion of concrete. Therefore, the role of STA is to make the concrete hydrophobic. Figure 4 (c) shows the static water droplet appearance on the surface of superhydrophobic concrete (SC) with different STA contents. It can be observed that adding different contents of STA to ordinary concrete (OC) will produce different degrees of hydrophobic modification on its surface. This is because the hydrophobic modified concrete has both micro / nano rough structure and low surface energy. This helps to form a solid-liquid hierarchical structure between the water droplet and the concrete surface, and then form air pockets of different sizes to prevent water droplet penetration.

[0045] Among them, SC with STA content of 4% showed the best wetting performance. The water contact angle (WCA) of SC-4 with STA content of 4% was 155° and the sliding angle (SA) was 8°. Figure 4 .(ab) As shown. The photos taken by the high-speed camera show that the water immediately bounces off the sample surface when it flows onto the sample surface ( Figure 4(b)). This is because there are trapped “air pockets” in the hierarchical micro / nanostructures. When a water droplet falls on the SC surface with a STA content of 4%, it is difficult for the water droplet to stay on it due to the low adhesion of the surface.

[0046] Example 3

[0047] Mechanical properties test:

[0048] The green super-hydrophobic concrete (SC-4) with anti-seepage and self-healing properties prepared in Example 1 was subjected to mechanical property tests:

[0049] Different from the surface modification method, bulk modified superhydrophobic concrete is a modification method from the inside out. Figure 5 .(a) shows the compressive strength of the modified green superhydrophobic concrete (SC-4) and conventional concrete (OC). The compressive strength of SC-4 at 3 days, 7 days and 28 days was 9.85 MPa, 11.27 MPa and 29.83 MPa, respectively. The compressive strength of OC at 3 days, 7 days and 28 days was 15.13 MPa, 23.60 MPa and 40.17 MPa, respectively. It can be observed that the compressive strength of SC-4 and OC both continue to increase with the increase of hardening time, but the compressive strength growth rate of SC-4 is slightly lower than that of OC. Figure 5 As shown in (b), the flexural strength of SC-4 at 3 days, 7 days and 28 days is 3.75 MPa, 4.13 MPa and 5.47 MPa, respectively. The flexural strength of OC at 3 days, 7 days and 28 days is 3.82 MPa, 4.24 MPa and 7.19 MPa, respectively. Especially when the age is 3 days and 7 days, the difference in flexural strength between SC-4 and OC is very small. This shows that the prepared samples have good mechanical properties. Based on these, SC-4 shows obvious overall stability, which will bring great potential for practical engineering applications.

[0050] Example 4

[0051] Water absorption test of samples:

[0052] The green super-hydrophobic concrete (SC-4) with anti-seepage and self-healing properties prepared in Example 1 was tested for water absorption:

[0053] The impermeability of concrete is crucial in engineering applications. Here, we completely immersed each surface of 28-day-old ordinary concrete (OC), superhydrophobic concrete (SC(PDMS)), and green superhydrophobic concrete SC-4 in a deionized water solution. The samples were taken out every two hours and weighed after removing the surface moisture. The test period was 72 hours. The results are shown in Figure 2. Figure 6.(a). It can be seen that during the early immersion period, the water absorption of OC increases rapidly, reaching 4.84% within 2 hours. During this period, SC-4 hardly absorbs water, only 0.23%. Comparing the water absorption of OC and SC-4, the water absorption of OC at 2 hours is about 21 times that of SC-4. The reason for this phenomenon is that water quickly penetrates into the internal space of OC through the capillary structure until the water fills the pores. From 2 hours to 12 hours, although the water absorption rate of OC slows down, it is still much higher than that of SC-4. Until 36 hours, the water absorption of OC reaches 6.26%, while that of SC is only 0.98%. Then, due to the saturation of internal water, the water absorption of OC changes slowly with the increase of immersion time. The water absorption of SC-4 increases compared with the initial level, but the change is not obvious. When the sample is immersed for 72 hours, the water absorption of OC finally reaches 6.67%, while that of SC is 1.66%. The water absorption of SC-4 is only about a quarter of that of OC, and its cumulative water absorption is 75% lower than that of OC.

[0054] To better illustrate the water-impermeability of SC-4, we also compared it with SC(PDMS), which has a certain degree of hydrophobicity. Figure 6 As shown in (b), during the process from 0 to 12 hours, the water absorption trends of SC-4 and SC(PDMS) are close to each other. At 12 hours, the water absorption change curves of the two hydrophobic concretes overlap and can reach 0.68%. After 12 hours, the average slope of the broken line of SC(PDMS) is higher than that of SC-4, so that the water absorption rate of SC(PDMS) remains greater than that of SC-4. Until 36 hours, the water absorption rates of SC(PDMS) and SC-4 reached 1.68% and 1.13%, respectively. After that, the water absorption growth rates of SC(PDMS) and SC-4 slowed down. Finally, the water absorption rate of SC(PDMS) reached 1.81% at 72 hours, while the cumulative water absorption rate of SC-4 was 8.3% lower than that of SC(PDMS).

[0055] Example 5

[0056] NaCl absorption rate test of samples:

[0057] The green super-hydrophobic concrete (SC-4) with anti-seepage and self-healing properties prepared in Example 1 was tested for NaCl absorption rate:

[0058] Similarly, conventional concrete (OC) and green superhydrophobic concrete (SC-4) were also completely immersed in 3.5% NaCl solution to test the NaCl absorption rate of the samples. Figure 7 (a) shows the NaCl absorption trend of OC and SC-4 during the entire immersion period. Figure 6.(a) are basically the same. At 72 hours, the absorption rate of OC reached 7.51%, and that of SC-4 reached 1.72%. The absorption rate of SC-4 was only about one-fifth of that of OC, and its cumulative NaCl absorption rate was 77% lower than that of OC. In addition, Figure 7 As shown in (b), the NaCl absorption of SC(PDMS) and SC-4 is also similar to Figure 6 .(b) is similar. The whole absorption process also shows a trend that the absorption first grows rapidly and then slows down. At 72 hours, the absorption of SC(PDMS) reaches 1.87%, while the cumulative NaCl absorption rate of SC-4 is 8% lower than that of SC(PDMS). These results show that SC-4 has superior inhibition to both water and NaCl compared with ordinary concrete OC and hydrophobic concrete SC(PDMS). This is attributed to the superhydrophobicity of the sample, which allows it to produce a double-layer "stagnant air pocket" in the rough joints in a micro / nano Cassie coupling state when in contact with water, which can prevent water penetration.

[0059] Example 6

[0060] Mechanical sustainability experiments:

[0061] The green super-hydrophobic concrete (SC-4) with anti-seepage and self-healing properties prepared in Example 1 was subjected to a mechanical wear test:

[0062] In practical applications, superhydrophobic surfaces are often susceptible to high external loads. More importantly, if the newly exposed surface after wear is not hydrophobic, concrete is more likely to be damaged by corrosion. Therefore, it is of great practical significance that superhydrophobic concrete maintains strong water repellency after mechanical wear. Figure 8 As shown in (b), our laboratory conducted the experiment using a standard friction resistance tester. During the test, the sample (28 days old) was rubbed back and forth with 1000-grit sandpaper (area 2×2 square centimeters) under a load of 250 grams. Under a pressure of 6.25 kPa, the sample was rubbed back and forth 200 times, with a wear distance of 5 cm each time. Figure 8 As shown in (a), there is no obvious change in the sample surface and thickness before and after wear. More importantly, Figure 8 (c) It can be observed that after 200 abrasions, water droplets still tend to stay on the newly exposed SC-4 surface instead of penetrating into it. This indicates that even after high-intensity abrasion, the newly exposed surface still has good superhydrophobicity like the original surface. This phenomenon also demonstrates the good self-healing properties of SC-4.

[0063] exist Figure 8In (d), the sample shows that the water contact angle (WCA) rises and falls repeatedly during 200 wear cycles, but basically remains between 150° and 155°. Similarly, the sliding angle (SA) changes from 5° to 10°. The wettability changes very little during the wear process. This is because PDMS uses its siloxane functional groups to react with the hydroxyl groups on the cement surface and forms a bond with the cement surface through Si-O bonds (a "ribbon" structure). This reaction greatly helps SC-4 improve its anti-friction ability and ensures its superhydrophobicity.

[0064] Example 7

[0065] Mechanical properties of samples after mechanical wear:

[0066] The mechanical properties of the green super-hydrophobic concrete (SC-4) with anti-permeability and self-healing properties after wear in Example 6 were tested:

[0067] To further evaluate the anti-friction property of green superhydrophobic concrete (SC-4), we also tested the mechanical properties of SC-4 before and after abrasion (3 days, 7 days, and 28 days). Fig. 9 As shown in (a), the compressive strength of SC-4 after wear at different ages did not change significantly compared with that before wear. After 200 wear cycles, the maximum decrease in compressive strength was 1.62 MPa, which occurred at an age of 3 days. After that, the difference gradually decreased with the increase of age. At 28 days, the compressive strength before and after wear reached 29.83 MPa and 29.57 MPa, respectively. Fig. 9 As shown in (b), the flexural strength of SC-4 remains almost unchanged before and after wear. After 200 wear cycles, the maximum drop in flexural strength is 0.26 MPa, which also occurs at the age of 3 days. After that, the difference gradually decreases with the increase of age. At 28 days, the flexural strength before and after wear reaches 5.47 MPa and 5.42 MPa, respectively. The above results show that mechanical wear has little effect on the SC-4 prepared by this scheme, both in terms of wettability and mechanical properties. Overall, SC-4 exhibits excellent mechanical sustainability and self-healing properties:

[0068] Example 8

[0069] UV aging experiment:

[0070] The green super-hydrophobic concrete (SC-4) with anti-seepage and self-healing properties prepared in Example 1 was subjected to an ultraviolet (340nm) aging experiment:

[0071] In outdoor applications, UV radiation is considered to be one of the main factors that affect the long-term stability of superhydrophobic surfaces and shorten their service life. In this work, the resistance of SC-4 to UV radiation was investigated. Fig.10 As shown in (b), it can be seen that even after continuous exposure to UV radiation for more than 120 hours, the water contact angle (WCA) of the sample always remains above 150° and the sliding angle (SA) is less than 15°. The average WCA of SC-4 is about 152° and the average SA is about 9.5°. We also tested the compressive and flexural resistance of SC-4 after aging. Fig.10 As shown in (c), the compressive strength of SC-4 after aging was 5.18, 8.13, and 27.46 MPa, respectively. Compared with the control group, the compressive strength of SC-4 decreased by 4.67, 3.14, and 2.37 MPa, respectively. It can be seen that the decrease in compressive strength values ​​decreases with the increase in aging time. Finally, the decrease in compressive strength of SC-4 after aging at 28 days was about 7.9%. Fig.10 As shown in (d), the flexural strength of SC-4 after aging was 2.84, 3.16 and 5.23 MPa, respectively. Compared with the control group, the flexural strength of SC-4 decreased by 4.67, 3.14 and 2.37 MPa, respectively. Similar to the change in compressive strength, the decrease in flexural strength also decreases with the increase in aging time. The decrease in flexural strength of SC-4 after aging at 28 days old was about 4.4%. The results of UV aging test show that SC-4 performs well in anti-UV aging and shows significant UV resistance.

Claims

1. A green super-hydrophobic concrete with anti-seepage and self-healing properties, characterized in that: The green super-hydrophobic concrete material only needs to mix and stir the modifying reagents stearic acid, polydimethylsiloxane and ethyl acetate with cement, sand and water to obtain super-hydrophobic cement mortar through the bulk modification method. The super-hydrophobic cement mortar is further poured into a mold and vibrated to harden it. After 3, 7 and 28 days of curing, a green super-hydrophobic concrete with impermeability and self-healing properties can be obtained.

2. A green super-hydrophobic concrete with anti-seepage and self-healing properties, comprising the following steps: S1. Preparation of fluorine-free waterproofing agent: adding polydimethylsiloxane and stearic acid into a beaker in a certain proportion to form a fluorine-free waterproofing agent; S2, preparation of the waterproofing agent mixture: continue to add ethyl acetate to the beaker to disperse the fluorine-free waterproofing agent, and obtain the fluorine-free waterproofing agent mixture by stirring for 10 minutes using a magnetic stirrer and ultrasonic dispersion for 30 minutes; S3. Preparation of super-hydrophobic cement mortar: 360 g of standard sand, 120 g of cement and 60 g of tap water (water-cement ratio of 0.5) were stirred at a slow speed in a cement mortar mixer for 5 minutes. The waterproofing agent mixture was poured into the mixer and further stirred at a high speed for 3 minutes to ensure that the fluorine-free waterproofing agent was evenly dispersed in the cement mortar to obtain super-hydrophobic cement mortar. S4, mold cleaning: 40×40×160mm 3 and 40×40×40mm 3 The mold is cleaned and dried, placed in a plasma machine, and treated at a power of 500-600W for 100-120s; S5, placing the cleaned stand-by mold on a vibration table, pouring the super-hydrophobic cement mortar described in step S3 into it and vibrating and compacting it for 2 minutes; S6. After 24 hours, the hardened samples were taken out and placed in a curing room at a temperature of 25°C and a relative humidity of 95% for curing for 3, 7 and 28 days, and finally a green super-hydrophobic concrete with impermeability and self-healing properties was obtained.

3. The method for preparing green super hydrophobic concrete with anti-seepage and self-healing properties according to claim 2 is characterized in that: The mass ratio of polydimethylsiloxane to stearic acid in step S1 is 0.5-4.5:0.58-30.69; the mass ratio of polydimethylsiloxane, stearic acid and ethyl acetate in step S2 is 0.5-4.5:0.58-30.69:5.07-30.42; the mass ratio of standard sand, cement and tap water in step S3 is 3:2:

1.

4. The method for preparing green super-hydrophobic concrete with anti-seepage and self-healing properties according to claim 2, characterized in that: In step S4, the cleaned stand-by mold is placed on a flat workbench; the super-hydrophobic cement mortar described in step S3 is poured into exactly the same mold, and the super-hydrophobic cement mortar is stirred at a uniform speed for 2 minutes using a glass rod, so that the super-hydrophobic cement mortar is evenly spread from the center to the surrounding of the mold until the super-hydrophobic cement mortar completely fills the mold.

5. The method for preparing green super-hydrophobic concrete with anti-seepage and self-healing properties according to claim 4, characterized in that: Put 3 molds (40×40×160mm 3 ) is placed on a standard vibration table and vibrated and compacted at a constant speed for 2 minutes.

6. The method for preparing green super-hydrophobic concrete with anti-seepage and self-healing properties according to claim 5, characterized in that: 3 molds (40×40×160mm 3 ) is filled with 2084kg / m 3 .

7. The method for preparing green super-hydrophobic concrete with anti-seepage and self-healing properties according to claim 4, characterized in that: Put 3 molds (40×40×40mm 3 ) is placed on a standard vibration table and vibrated and compacted at a constant speed for 2 minutes.

8. The method for preparing green super-hydrophobic concrete with anti-seepage and self-healing properties according to claim 5, characterized in that: 3 molds (40×40×40mm 3 ) is filled with 2084kg / m 3 .

9. The method for preparing green super-hydrophobic concrete with anti-seepage and self-healing properties according to claim 2, characterized in that: In step S6, the hardened sample is placed in a curing room at a temperature of 25° C. and a relative humidity of 95% for continuous curing for 3, 7 and 28 days, and finally a green super-hydrophobic concrete with impermeability and self-healing properties is obtained.